STRUKTUR DAN KOMPOSISI VEGETASI HUTAN MANGROVE DI NEGERI RUTONG KECAMATAN LEITIMUR SELATAN KOTA AMBON - Herdin Paluppa; Ludia Siahaya; Moda Talaohu (MARSEGU : Jurnal Sains dan Teknologi, 2025)
The structure and composition of mangrove vegetation in Negeri Rutong, Leitimur Selatan District, Ambon City are the primary focus of this research. The methodology used is a quantitative approach, which involves the use of numerical data throughout all stages of the research, from data collection to data analysis. The data collected are primary data obtained directly from the field through vegetation studies. The research findings on the structure and composition of mangrove vegetation indicate the presence of three true major mangroves and two minor mangrove species that form the vegetation composition in Negeri Rutong. These include: Avicennia lanata, Sonneratia alba, Rhizophora apiculata, Scyphiphora hydrophyllacea, and Xylocarpus granatum. The vertical structure of the mangrove forest in Negeri Rutong consists of two strata. The Important Value Index (IVI) for the seedling level shows that Avicennia lanata has the highest value, at 45.26%. At the sapling level, Sonneratia alba has the highest IVI at 55.63%, and at the tree level, Sonneratia alba also dominates with an IVI of 134.88%.